A race against time – an evaluation of lifesaving treatment pathways for patients following cardiac arrest in a non-hospital setting. - Rowena Bailey; Laura Herbert; Richard Pugh; Ronan Lyons; Tamas Tszakmany (International Journal of Population Data Science, 2024)
Background Cardiac arrest occurs when the heart ceases pumping blood around the body. Most take place outside hospital. A sequence of effective interventions (a “chain of survival”) is essential for patient survival and recovery of organ function. Out of Hospital Cardiac Arrest (OHCA) requires prompt recognition and call for help, proficient CPR, early defibrillation and conveyance by the emergency services to an appropriate hospital. If initial resuscitation is successful, effective post-resuscitation care is required, delivered usually in the intensive care unit (ICU). New patient pathways were introduced following an update to national guidelines, which recommend conveyance of patients to centres with percutaneous coronary intervention (PCI) services where possible.